The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1002/jgm.508
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid DNA electrotransfer for intracellular and secreted proteins expression: new methodological developments and applications

Abstract: SummaryIn vivo electrotransfer is a physical method of gene delivery in various tissues and organs, relying on the injection of a plasmid DNA followed by electric pulse delivery. The importance of the association between cell permeabilization and DNA electrophoresis for electrotransfer efficiency has been highlighted. In vivo electrotransfer is of special interest since it is the most efficient non-viral strategy of gene delivery and also because of its low cost, easiness of realization and safety. The potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
72
0
7

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(85 citation statements)
references
References 91 publications
6
72
0
7
Order By: Relevance
“…8 For nonviral transfection, the naked DNA can be delivered into cells or tissues either by chemical carriers such as liposome and cationic polymers or by physical/ mechanical means exemplified by electroporation. 9,10 Effective use of these methods is limited by the low transfection efficiency, the transient expression of gene product and the lack of organ and tissue specificity. Previous studies have suggested that sonoporation (transient increase in cell membrane permeability by ultrasonic exposure) could be an alternative approach as it is not only rapid, reproducible and relatively inexpensive but also provides a safe, noninvasive and efficient means suitable for in vivo gene delivery.…”
Section: Introductionmentioning
confidence: 99%
“…8 For nonviral transfection, the naked DNA can be delivered into cells or tissues either by chemical carriers such as liposome and cationic polymers or by physical/ mechanical means exemplified by electroporation. 9,10 Effective use of these methods is limited by the low transfection efficiency, the transient expression of gene product and the lack of organ and tissue specificity. Previous studies have suggested that sonoporation (transient increase in cell membrane permeability by ultrasonic exposure) could be an alternative approach as it is not only rapid, reproducible and relatively inexpensive but also provides a safe, noninvasive and efficient means suitable for in vivo gene delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a wide range of tissues have been studied including skin, kidney, lung, liver, skeletal and cardiac muscle, joints, spinal cord, brain, retina, cornea and the vasculature. [4][5][6][7] In most studies, electroporation increased gene expression by 100-to 1000-fold compared to injection of naked plasmid DNA. The exact mechanism by which delivery of plasmid into cells is enhanced is not certain, although it is clear that membranes become effectively permeable once a critical voltage has been achieved (in the order of 200 V/cm in vivo).…”
Section: Application Of An Electrical Field Dramatically Enhances Plamentioning
confidence: 99%
“…1 Some applications of ET now envisioned are the endogenous synthesis of EPO, 2 of the soluble receptor to TNFa 3 and of the antiinflammatory cytokine IL-10, 4,5 as well as tumour gene therapy, 6,7 restoration of muscle structural proteins, 8 and DNA vaccination. 9 ET is also applied to tumour electrochemotherapy, 10 where protocols with high voltage and short duration pulses allow antitumoral drugs to be locally delivered to tumour cells.…”
Section: Introductionmentioning
confidence: 99%